Some Concepts and Theorems of Uncertain Random Process. Issue 1 (29th September 2014) - Gao, Jinwu; Yao, Kai; Yang, Lixing; Li, Xiang; Ralescu, Dan A.
<x xml:space="preserve">Abstract</x> To deal with a system with both randomness and uncertainty, chance theory has been built and an uncertain random variable has been proposed as a generalization of random variable and uncertain variable. Correspondingly, as a generalization of both the stochastic process and the uncertain process, this paper will propose an uncertain random process. In addition, some special types of uncertain random processes such as stationary increment process and renewal process will also be discussed.